Association Between Prognostic Nutritional Index and Clinical Outcomes in Advanced Non-Small Cell Lung Cancer Treated with Immune Checkpoint Inhibitors - Altıntaş, Yunus Emre; Kınıkoğlu, Oğuzcan; Işık, Deniz; Özkerim, Uğur; Öksüz, Sıla; Tünbekici, Salih; Başoğlu, Tuğba; Sürmeli, Heves; Odabaş, Hatice; Turan, Nedim (Cerrahpaşa Medical Journal, 2025)
Objective: The Prognostic Nutritional Index (PNI), an inflammation-based biomarker derived from serum albumin and lymphocyte count, reflects both nutritional and immunological status. Although widely studied in gastrointestinal malignancies, its prognostic value in non-small cell lung cancer (NSCLC) patients receiving immune checkpoint inhibitors (ICIs) remains insufficiently explored. Methods: A retrospective cohort of 263 patients diagnosed with stage IV non-small-cell lung cancer (NSCLC) who received ICIs (ICIs) between March 2018 and May 2024 at a single tertiary institution was evaluated. The PNI was computed using pre-treatment laboratory data obtained prior to immunotherapy initiation. Patients were categorized into high (≥45.32) and low (<45.32) PNI groups, with the cut-off value determined through receiver operating characteristic (ROC) curve analysis. Survival outcomes were assessed using Kaplan–Meier and Cox regression analyses. Radiological responses were also compared between groups. Results: Patients in the high PNI group demonstrated a markedly prolonged median overall survival (OS) compared to those in the low PNI group (14.17 vs. 6.07 months; log-rank test, P < .001). In multivariate Cox regression analysis, a high PNI was identified as an independent predictor of improved OS (hazard ratio [HR] = 0.48; 95% CI: 0.34-0.67; P < .001). While patients with elevated PNI also exhibited a trend toward longer progression-free survival (6.80 vs. 5.03 months), this finding did not reach statistical significance (P = .14). Radiologic response rates were more favorable in the high PNI group, with higher rates of partial and complete response. Conclusion: Pretreatment PNI is an independent prognostic factor for OS in patients with advanced NSCLC treated with ICIs. Its ease of calculation, low cost, and reflection of host immune-nutritional status support its potential integration into routine clinical practice to refine risk stratification and guide supportive interventions. Cite this article as: Altıntaş YE, Kınıkoğlu O, Işık D, et al. Association between prognostic nutritional index and clinical outcomes in advanced non-small-cell lung cancer treated with immune checkpoint inhibitors. Cerrahpaşa Med J 2025, 49, 0030, doi: 10.5152/ cjm.2025.25030.